2016
DOI: 10.5812/ircmj.30874
|View full text |Cite
|
Sign up to set email alerts
|

Patient Safety Culture and Factors that Impact That Culture in Tehran Hospitals in 2013

Abstract: Background: Sufficient evidence is lacking about patient safety culture in Iran. It is only by focusing on the culture of safety within healthcare and treatment institutes that improvements may be made in patient care services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
7
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 34 publications
8
7
2
Order By: Relevance
“…A previous Iranian study conducted in an academic intensive care unit [46], like the results in this study, found that all dimensions needed to be improved. These findings contrast with those of Habibi et al (2016) where a higher PRR score was found in teaching hospitals in Tehran [47]. A recent Iranian systematic review illustrates that, compared to the results of studies conducted in other countries, the mean of the responses in Iran for the different dimensions of PSC is low, a finding which underlines the fact that, for many people working in Iranian hospitals (including the managers), the concepts of PSC are unknown [48].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…A previous Iranian study conducted in an academic intensive care unit [46], like the results in this study, found that all dimensions needed to be improved. These findings contrast with those of Habibi et al (2016) where a higher PRR score was found in teaching hospitals in Tehran [47]. A recent Iranian systematic review illustrates that, compared to the results of studies conducted in other countries, the mean of the responses in Iran for the different dimensions of PSC is low, a finding which underlines the fact that, for many people working in Iranian hospitals (including the managers), the concepts of PSC are unknown [48].…”
Section: Discussioncontrasting
confidence: 99%
“…"Non-punitive response to error" had the lowest PRR, a finding which follows an earlier study conducted in a public hospital in Tabriz and which examined the same issues [51]. These findings are consistent with other local findings [47] and those from international studies [10,16,52], and would suggest that a major barrier to error reporting is the risk of a punitive response. When non-punitive measures are taken, errors will be detected and reported early and further occurrences will be prevented [53].…”
Section: Discussionsupporting
confidence: 86%
“…A previous Iranian study conducted in an academic intensive care unit [46], like the results in this study, found that all dimensions needed to be improved. These ndings contrast with those of Habibi et al (2016) where a higher PRR score was found in teaching hospitals in Tehran [47]. A recent Iranian systematic review illustrates that, compared to the results of studies conducted in other countries, the mean of the responses in Iran for the different dimensions of PSC is low, a nding which underlines the fact that, for many people working in Iranian hospitals (including the managers), the concepts of PSC are unknown [48].…”
Section: Discussioncontrasting
confidence: 97%
“…"Non-punitive response to error" had the lowest PRR, a nding which follows an earlier study conducted in a public hospital in Tabriz and which examined the same issues [52]. These ndings are consistent with other local ndings [47] and those from international studies [16,50,53], and would suggest that a major barrier to error reporting is the risk of a punitive response. When non-punitive measures are taken, errors will be detected and reported early and further occurrences will be prevented [54].…”
Section: Discussionsupporting
confidence: 84%
“…A previous Iranian study conducted in an academic intensive care unit [42], like the results in this study, found that all dimensions needed to be improved. These findings contrast with those of Habibi et al (2016) where a higher PRR score was found in teaching hospitals in Tehran [43]. A recent Iranian systematic review illustrates that, compared to the results of studies conducted in other countries, the mean of the responses in Iran for the different dimensions of PSC is low a finding which underlines the fact that, for many people working in Iranian hospitals (including the managers), the concepts of PSC are unknown [44].…”
Section: Discussionmentioning
confidence: 70%